Manifestação da oralidade em contos contemporâneos: organização e interação nos diálogos literários - Siqueira, Neusa Lucas de (2006)
This research about the spoken language expression on the written has lead to papers, thesis and articles, whose objects of study have been, in the most time, chronic and theater plays. The short story has been few studied. The objective of this work is to analysis the spoken language expression in the literary dialogues, specificly, the short-story, based on Conversation Analysis and Interactional Sociolinguistic. At this study, we checked how happen the local and global organizations of this dialogues and how happen the interaction of the interecters in this dialogues, specificly, the politeness strategies, the footing and the frame of the character to reach an effective interactional process. The Corpus is constituted for three contemporary shorts stories A porta está aberta by Luiz Vilela, Entrevista and Os Prisioneiros by Rubem Fonseca. We may give preference to the shorts stories of Century XX because of their contemporarity and because they show examples closer of our present-day reality. To reach our objectives, we lean on theorics like Fávero, Andrade and Aquino (2002), Bakhtin (2000), Brown Levinson (1996), Goffman (1974), Marcuschi (2003), among others. Our analyses let us to prove that the short-story is an example of hybrid genre, since it shows its own caracteristics of spoken, allied to the written language. Beside this, the dialogues, at this writing, may be examples of communications competence modals close of a natural dialogue. We hope, with the results presented here, help to the studies about Spoken and Written Language